Altruism Atas Kapal KM Selayang Pandang - Suryani, Dedeh; Hendrawan, Andi; Pramono, Sri (Universitas Ivet, 2024)
Most research on altruism has not attempted to prove the existence of altruism. However, the problems associated with identifying altruism have not escaped the attention of researchers. An examination of the contribution of altruism studies to the understanding of social behavior, personality. The research method used was observation using 35 samples of crew members from the KM ship at a glance. The results of the research show that the majority of Selayang Pandang Ship Crews behave in altruism, which will improve performance